New english file : - Oxenden, Clive (Oxford University Press, 2004)
The CD-ROM part of the CD contains the videos from the New English File video program available in both DVD and VHS format. If you play the MultiROM on a regular CD player, one of the sections will be the Mini-Phrasebook, in which, when you hear a sentence, you respond to it.